Processing and cytocompatibility of Cu-doped and undoped fluoride-containing bioactive glasses - Nawaz, Qaisar; Blaeß, C.; Müller, R.; Boccaccini, Aldo R. (Open Ceramics, 2024)
Sintered or additive-manufactured bioactive glass (BG) scaffolds are highly interesting for bone replacement applications. However, crystallization often limits the high-temperature processability of bioactive glasses (BGs). Thus, the BG composition must combine high bioactivity and processability. In this study, three BGs with nominal molar (%) compositions 54.6SiO2-1.7P2O3-22.1CaO-6.0Na2O-7.9K2O-7.7MgO (13–93), 44.8SiO2-2.5P2O3-36.5CaO-6.6Na2O-6.6K2O-3.0CaF2 (F3) and 44.8SiO2-2.5P2O3-35.5CaO-6.6Na2O-6.6K2O-3.0CaF2-1.0CuO (F3–Cu) were investigated. The dissolution and ion release kinetics were investigated on milled glass powder and crystallized particles (500–600 μm). All glasses showed the precipitation of hydroxyapatite (HAp) crystals after 7 days of immersion in simulated body fluid. No significant differences in ion release from glass and crystalline samples were detected. The influence of surface roughness on cytocompatibility and growth of pre-osteoblast cells (MC3T3-E1) was investigated on sintered and polished BG pellets. Results showed that sintered BG pellets were cytocompatible, and cells were seen to be well attached and spread on the surface after 5 days of incubation. The results showed an inverse relation of cell viability with the surface roughness of pellets, and cells were seen to attach and spread along the direction of scratches.
CRIS-Team Scopus Importer:2024-04-12
Keywords: Bioactive glass; Crystallization; Cytocompatibility; Solubility; Surface roughness